Involvement of Epigenetic Mechanisms and Non-coding RNAs in Blood-Brain Barrier and Neurovascular Unit Injury and Recovery After Stroke - Stamatovic, Svetlana M.; Phillips, Chelsea M.; Martinez-Revollar, Gabriela; Keep, Richard F.; Andjelkovic, Anuska V. (Frontiers in Neuroscience, 2019)
Cessation of blood flow leads to a complex cascade of pathophysiological events at the blood-vascular-parenchymal interface which evolves over time and space, and results in damage to neural cells and edema formation. Cerebral ischemic injury evokes a profound and deleterious upregulation in inflammation and triggers multiple cell death pathways, but it also induces a series of the events associated with regenerative responses, including vascular remodeling, angiogenesis and neurogenesis. Emerging evidence suggests that epigenetic reprograming could play a pivotal role in ongoing post-stroke neurovascular unit changes and recovery. This review summarizes current knowledge about post-stroke recovery processes at the neurovascular unit, as well as epigenetic mechanisms and modifiers (e.g. DNA methylation, histone modifying enzymes and microRNAs) associated with stroke injury and neurovascular unit repair. It also discusses novel drug targets and therapeutic strategies for enhancing post-stroke recovery.